Pembiayaan Murabahah dan Profitabilitas PT. Bank Aceh Syariah Tahun 2017-2020 - Liza, Laisa; Hilwa, Saviratul (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aimed to test the effect of Murabaha financing on profitability in PT. Islamic Banks. The data analysis method in this study uses simple linear regression to predict the influence of independent variables. This study uses a documentation method in collecting data. The data of this study is financial statements from January 2017 to December 2021, with a total of 48 data which is population data. The results showed that H0 was rejected and Ha was accepted. With these results, it can be concluded that Murabaha financing significantly affects profitability (ROA) in PT. Bank Aceh Syariah in 2017-2020 means that if the value of Murabaha financing increases, it will increase profits.